Job Satisfaction among Healthcare Workers in a Tertiary Center in Kano, Northwestern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Job satisfaction has been associated with lots of benefits. The provision of health services depends on several factors but the availability and retention of human resources is particularly important. This study aims to determine job satisfaction among healthcare workers in a tertiary hospital in Kano and find if there are any, determining or related factors.Materials and Methods:This was a cross-sectional study conducted between May and June, 2017 on health workers working at a tertiary hospital in Kano, Nigeria. A modified closed-ended self-administered job satisfaction survey questionnaire was used. Data collected were analyzed with IBM Statistical Package for the Social Sciences, version 21 Windows statistical software.Results:The participants’ ages ranged from 18 to 62 years with a mean age of 38.94 ± 8.07 years. There were 119 (74.4%) males and 41 (25.4%) females with a male/female (M:F) ratio of 3:1 (χ2= 19.415;P= 0.000). Overall, out of the 157 (98.1%) of the participants that responded to the job satisfaction question, 142 (90.4%) indicated they were satisfied with their jobs and 15 (9.6%) were dissatisfied. Satisfaction based on sociodemographic variables showed that there were no significant associations between them. There were also no significant associations between the professional categories, years in service, monthly salary, job schedule of the participants, and job satisfaction. The main reasons for job satisfaction were monetary and service to humanity.Conclusion:Majority of health workers in Kano were highly satisfied with their jobs because of the need to serve and also for the income.